WWII a chronicle of soldiering - Jones, James 1921-1977 (University of Chicago Press, 2014)
This "unique and fascinating" WWII memoir by the acclaimed author of From Here to Eternity and The Thin Red Line "stands out as one of the most vivid" (The Wall Street Journal). In 1975, James Jones was chosen to write the text for an oversized coffee table book featuring visual art from World War II. The book was a best seller, praised for both its images and for Jones's text. In subsequent decades, when it became impossible to reproduce the book with its original artwork, it fell out of print and was forgotten. But now, this edition of WWII makes Jones's stunning text'his only extended nonfiction writing on the war'available once again. Moving chronologically and thematically through the complex history of World War II, Jones interweaves his own vivid memories of soldiering in the Pacific'from the look on a Japanese fighter pilot's face as he bombed Pearl Harbor, so close that Jones could see him smile and wave, to hitting the beach under fire in Guadalcanal'while always returning to resounding larger themes. While much of WWII is a tribute to the commitment of American soldiers, Jones also pulls no punches when recounting questionable strategic choices, wartime suffering, disorganization, the needless loss of life, and the brutal realization that a soldier is merely a cog in a heartless machine.